Dialogues and disputes in biblical disguise from late antiquity to the Middle Ages - Tóth, P (Routledge, 2021)
Dialogues and Disputes in Biblical Disguise from Late Antiquity to the Middle Ages offers the first overall discussion of the hitherto under-studied literary genre of pseudo-biblical dialogues. The essays presented here analyse texts, which transform dialogues and disputations about contemporary theological, legal or philosophical matters into a biblical scenario as discussions between biblical characters. Such dialogues, involving demonic, human and divine figures, are common and popular in the Oriental (Syriac, Coptic and Arabic) as well as Greek, Latin and medieval vernacular literatures, in prose and poetry alike, from late antiquity to the early modern. The present volume is the first attempt for a systematic and interdisciplinary study of this literature in the form of thematically organized essays by some of the most eminent experts on late antique and medieval dialogic texts in a wide range of traditions. Presenting surveys of pseudo-biblical dialogues in various languages and cultures, the volume will foster a new interdisciplinary approach to these texts previously investigated in isolation within the individual scholarly fields of Oriental, Byzantine, Medieval or Slavonic studies. It also endeavours to create new methodologies for their investigation informed by and also impacting both literary and biblical studies. Analysing the interplay between content and literary form, the contributions present an overview of the development of pseudo-biblical dialogues from Syriac, Coptic and Greek patristics to not only Medieval Latin and Byzantine but also Slavonic, Arabic and English texts, providing us with the first manual about this wide-spread and popular, but unexplored literature.